Pemanfaatan Instagram bagi Pengembangan Pemasaran Usaha Mikro Kecil dan Menengah di Banjarbaru - Sudirwo, Sudirwo; Nurriqli, Arifia; Risanta, Muhammad (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2021)
Many micro, small and medium enterprises (MSMEs) still sell products conventionally and few have used e-commerce. So that not all products from MSMEs are widely known by the public. Al-Firdaus Borneo is a MSME player engaged in woven handicrafts made from purun plants which has been running for about two years in utilizing Instagram social media with an account @pengrajinanyamanpurunalfirdaus. The method used in this research is descriptive qualitative, in which the researcher tries to describe and analyze specifically the data obtained in the field in accordance with the focus of the problem to be studied. Information and data obtained by researchers through interviews with craftsmen as well as account owners who are the object of research and through observations made during the research activities in progress. Based on this research, it was found that the use of Instagram social media had a positive impact on the development of Al Firdaus product marketing so that Instagram followers and sales increased. In addition, the operation is easy and has many users so that it becomes a practical promotional media, which is cheap, reliable and can reach all users everywhere. However, there are still some obstacles and weaknesses encountered, namely poor internet access in the account owner area, lack of expertise of the account owner in making good and attractive designs, and product prices are not raised so they have to communicate through the contacts provided.